Intra-industry information releases - Clinch, Greg J.; Sinclair, Norman A. (Journal of Accounting and Economics, 1987)
This paper investigates the extent of intra-industry information transfers associated with the half-yearly earnings announcements of a sample of Australian firms. The ‘omitted factor’ interpretation of Foster's (1981) results is examined using a recursive systems specification of the return generating process to model extra-market return covariation in cross-section. Although some aspects of the results do appear sensitive to the alternative methodologies, the overall conclusion is consistent with Foster (1981) and supports the existence of intra-industry information transfers associated with firms' earnings releases.